2016
DOI: 10.3989/gya.0559161
|View full text |Cite
|
Sign up to set email alerts
|

Study of volatile alcohols and esters from the subcutaneous fat during ripening of Iberian dry-cured ham. A tool for predicting the dry-curing time

Abstract: SUMMARY:Variations in the amounts of volatile alcohols and esters from subcutaneous fat have been assessed during the dry-curing process (1022 days) of Iberian ham according to a purge and trap-gas chromatography-mass spectroscopy method, using the same hams throughout the process. During processing time, the subcutaneous adipose tissues of ten hams obtained from five Iberian pigs fed on acorns and pasture were sampled and analyzed once per month. Fifteen alcohols and five esters have been identified. All vola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…Alcohols showed a very regular trend constantly increasing from R0 to S16 when the greatest amount for almost every compound was observed. The great increase of this family from green to seasoned fat of dry-cured ham is in accordance with results reported by Narváez-Rivas et al [ 47 ]. After the 16th month of seasoning, they dropped at lower values.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Alcohols showed a very regular trend constantly increasing from R0 to S16 when the greatest amount for almost every compound was observed. The great increase of this family from green to seasoned fat of dry-cured ham is in accordance with results reported by Narváez-Rivas et al [ 47 ]. After the 16th month of seasoning, they dropped at lower values.…”
Section: Resultssupporting
confidence: 92%
“…Flores et al [ 46 ] proposed that esters could also be formed from the interaction of free fatty acids and alcohols generated by lipid oxidation in intramuscular tissues. In our study twenty esters were observed, which is a quite high number if compared with results reported by several authors [ 38 , 47 ]. It is worth noting that most of the studies on ham employed samples of Biceps femoris or Semimembranosus muscles, in which the fat content was very low compared to our samples.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…The VC were classified based on their origin (lipolysis, proteolysis and microbial), according to Dainty, Edwards & Hibbard (1985), Roger, Degas & Gripon (1988), Ruiz et al (1999), Meynier et al (1999), Carrapiso et al (2002), Arnoldi (2003), Liu (2003), Machiels et al (2003), Raes et al (2003), Martín et al (2006), Ramírez & Cava (2007), Calkins & Hodgen (2007), Narváez-Rivas, Gallardo & León-Camacho (2012), Fonseca et al (2015), Rivas, Gallardo & Camacho (2016) and Pérez-Santaescolástica et al (2019).…”
Section: Methodsmentioning
confidence: 99%